The woodlanders - Hardy, Thomas, 1840-1928.; Wordsworth Classics (Hertfordshire : Wordsworth Classics, 2005)
When young Grace Melbury chooses the wrong suitor to marry the lives of her two loves and their entire community are affected.
Adult
Keywords: Arranged marriage -- Fiction; Forests and forestry -- Fiction; Social classes -- Fiction; Triangles (Interpersonal relations) -- Fiction; Interpersonal relations -- Fiction; Love stories; Marriage -- Fiction; Psychological fiction; Dorset (England) -- Fiction; England -- Social life and customs -- 19th century -- Fiction; Wessex (England) -- Fiction; England -- Social life and customs -- Fiction